Co-delivery of chlorantraniliprole and avermectin with a polylactide microcapsule formulation. Issue 43 (3rd July 2020) - Suraphan, Nuntanit; Fan, Linfeng; Liu, Baoxia; Wu, Decheng
Abstract : We constructed a porous PLA-microcapsule-based co-delivery system of chlorantraniliprole and avermectin using a double emulsion method combined with premix membrane emulsion. Abstract : Improving drug utilization of water-based pesticide formulations is facile and feasible to efficiently avoid serious pesticide residues and reduce the resulting environmental pollution. A co-delivery system of two- or multi-pesticides within one formulation could enhance drug efficiency and decrease usage amounts of pesticides due to the synergistic effect of the loaded multiple pesticides. Herein, we reported a porous polylactide (PLA) microcapsule formulation for co-delivery of avermectin (Av) and chlorantraniliprole (CAP). A double emulsion method combined with premix membrane emulsion (PME) was adopted to produce the Av/CAP-loaded porous microcapsules (Av/CAP P-MCs) with prolonged drug release, high loading content and entrapment efficiency, as well as good light and thermal stability. Compared with single Av- or CAP-loaded microcapsule formulations, the Av/CAP P-MCs exhibited higher biotoxicity against Plutella xylostella . These results reveal that the Av/CAP co-delivery system may be a promising candidate to be further explored as a facile, effective and environmentally-friendly pesticide formulation.